2015
DOI: 10.1021/am5086885
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Bioactivity of Mg–Nd–Zn–Zr Alloy Achieved with Nanoscale MgF2 Surface for Vascular Stent Application

Abstract: Magnesium (Mg) alloys have revolutionized the application of temporary load-bearing implants as they meet both engineering and medical requirements. However, rapid degradation of Mg alloys under physiological conditions remains the major obstacle hindering the wider use of Mg-based implants. Here we developed a simple method of preparing a nanoscale MgF2 film on Mg-Nd-Zn-Zr (denoted as JDBM) alloy, aiming to reduce the corrosion rate as well as improve the biological response. The corrosion rate of JDBM alloy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(63 citation statements)
references
References 39 publications
5
58
0
Order By: Relevance
“…23,24 Wang et al studied the corrosion of Mg alloy under dynamic fluid flow condition and found that the flow stress induced by fluid flow could accelerate the in vitro corrosion of Mg alloy. 25 Though the influences of Mg alloy on viability, proliferation, and function of cells have been extensively studied, [26][27][28] the converse question about the role of cells during Mg alloy corrosion has been barely examined. The infiltration of inflammatory cells and macrophage clusters was observed at the implantation site of Mg alloy implants both for vascular stent and orthopedic applications due to the host response.…”
Section: Martinez Sanchez Et Al Systematically Reviewed the In Vitromentioning
confidence: 99%
“…23,24 Wang et al studied the corrosion of Mg alloy under dynamic fluid flow condition and found that the flow stress induced by fluid flow could accelerate the in vitro corrosion of Mg alloy. 25 Though the influences of Mg alloy on viability, proliferation, and function of cells have been extensively studied, [26][27][28] the converse question about the role of cells during Mg alloy corrosion has been barely examined. The infiltration of inflammatory cells and macrophage clusters was observed at the implantation site of Mg alloy implants both for vascular stent and orthopedic applications due to the host response.…”
Section: Martinez Sanchez Et Al Systematically Reviewed the In Vitromentioning
confidence: 99%
“…The Nyquist plots of the three samples were similar except for the difference in the diameter of the loops, which consisted of one high frequency capacitance loop and one low frequency capacitance loop. The high‐frequency capacitive loop can be attributed to the charge transfer of the corrosion process . The capacitive loops for Mg 89 Zn 2 Y 4 Li 5 alloy exhibited a higher diameter in comparison with other two alloys.…”
Section: Resultsmentioning
confidence: 98%
“…Vascular magnesium alloy stents with reduced corrosion rates have been shown to be mechanically stable for up to 6 months in animal experiments and were eventually evaluated in clinical trials [97][98][99][100][101][102][103]. Polymer-coated drug-eluting magnesium stents (Magmaris and DREAMS; Biotronik AG, 231, Bülach, Switzerland) were commercially offered and claimed to be resorbed to 95% within a year in clinical trials.…”
Section: Characteristics Of Magnesium-based Implantsmentioning
confidence: 99%